Waylon & Willie [compact disc] - Jennings, Waylon (Original masters (Buddha Records), 2000)
"Waylon & Willie cemenented a partnership that is among the most enduring and successful in country music history. Released in the wake of the hugely successful Wanted! The Outlaws, which featured Jennings and Nelson along with Tompall Glaser and Jessi Colter, Waylon & Willie spawned two #1 country singles. The album enjoyed a three month run at #1 on the country chart, went Double Platinum, and stayed on the chart for over two years."--Container.